Cell-based neurorestorative therapy for postpoliomyelitis syndrome: a case report - Xi HT; Chen D (Journal of Neurorestoratology, 2016)
Haitao Xi,1,2,* Di Chen1,* 1Center of Neurorestoratology, Beijing Hongtianji Neuroscience Academy, 2Center of Neurorestoratology, Beijing Rehabilitation Hospital affiliated Capital Medical University, Beijing, People’s Republic of China *These authors contributed equally to this work Abstract: Postpoliomyelitis syndrome refers to the new neuromuscular symptoms that occur in patients, years after their acute poliomyelitis has stabilized. A 64-year-old Danish man presented with lower limb weakness and severe pain for 2 years and 5 months. He had a history of poliomyelitis affecting his limbs 59 years ago. Physical examination revealed atrophy of muscles of both lower limbs. Electromyography revealed that recruitment of maximal voluntary contraction of muscles was decreased in the affected muscles. He received cell-based neurorestorative therapy during admission, and then, his neurological function improved and remained stable during 4-year follow-up. This case report shows that cell therapy could be a treatment option for postpoliomyelitis syndrome. Keywords: postpoliomyelitis syndrome, neuromuscular disease, cell transplantation, cell-based neurorestorative therapy